Peran manajemen risiko dalam mengelola kewajiban pajak bagi usaha mikro, kecil, dan menengah (UMKM - Zidan, Muhamad (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the contribution of risk management implementation in managing tax obligations by Micro, Small and Medium Enterprises (MSMEs) in Indonesia. MSMEs are a strategic sector in the national economic structure, but still face serious challenges related to low tax compliance. Low tax literacy, limited resources, and minimal application of risk management principles are the main factors of non-compliance. Through a qualitative approach based on literature and documentation studies, this study found that the systematic application of risk management can increase fiscal awareness, improve financial governance, and reduce potential tax sanctions. In addition, strengthening strategies such as community-based tax education, reporting digitalization, and cross-sector collaboration are needed to encourage sustainable compliance. The results of this study are expected to provide theoretical and practical contributions for MSME actors and policymakers in creating a more adaptive and inclusive tax ecosystem.